The Act of Peter BG, 4: 128,1 - 141,7 (TAOPe) - Brashler, James (BrillOnline Reference Works, 2012)
The text is generally well preserved, with the following exceptions: a small lacuna in the middle of pp. 129-32, close to the outside margin; a large lacuna affecting the beginning of the last eight lines of p. 135 and the end of lines 11-14 on p. 136; a lacuna affecting most of the first lines of pp. 139-40; severe fading on p. 142 (the scribal post-script). In addition, all of pp. 133-34 is missing